Investigating SST diurnal variation and its response to the MJO in the North Indian Ocean using FY-4A data - Zhang, Xianliang; Mao, Zhihua; Zhang, Longwei; Sang, Xuan (Frontiers in Marine Science, 2025)
Sea surface temperature (SST) diurnal variation is an important part of air-sea energy exchange, and its response to the Madden–Julian Oscillation (MJO) also helps in studying the development mechanism of the MJO. This study investigates SST diurnal variation in the North Indian Ocean by employing hourly data from the FY-4A geostationary satellite, in conjunction with reanalysis products and the MJO index. Validation against in situ SST measurements shows a bias of –0.33°C, an absolute bias of 0.73°C, an RSD of 0.33°C, an RMSE of 0.94°C, and a correlation coefficient of 0.90. The results demonstrate consistent accuracy throughout the diurnal cycle. Diurnal warming is most pronounced in the northern Arabian Sea and northern Bay of Bengal, especially from March to May prior to the monsoon onset. Wind speed and shortwave flux emerge as key drivers, although wind speed exerts a stronger regional influence on diurnal warming. Furthermore, the SST diurnal variation responds to the MJO within 1–2 days, as its active phase increases cloud cover and intensifies wind, thereby suppressing daytime warming. Despite the high temporal resolution of FY-4A, which allows for detailed sub-daily observations, monsoonal circulation and cloud cover can reduce data availability, complicating quantitative studies of SST variability and MJO feedbacks. Therefore, integrating multiple data sources is crucial for comprehensive analyses. Overall, these findings underscore the potential of geostationary satellites for monitoring diurnal SST fluctuations and emphasize the necessity of accounting for complex atmospheric–oceanic interactions in the North Indian Ocean when examining the role of diurnal variation in broader climate processes.